STRATEGI PENYIARAN RADIO REPUBLIK INDONESIA SURAKARTA UNTUK MENJANGKAU PERDESAAN MELALUI PROGRAM SIARAN PEDESAAN - Dhiva Pridayuliamita; Erwin Kartinawati; Sofia Ningsih Rahayu Putri (JURNAL ASSOSIATIV, 2023)
Radio is a mass communication medium that has long been present among the people of Indonesia. Radio Republik Indonesia is a public broadcasting institution whose function is to provide information broadcast services, healthy entertainment education, and social control. The research entitled "Republic of Indonesia Radio Broadcasting Strategy Surakarta To Reach Rural Through Rural Broadcasting Program" aims to describe how the strategy adopted by RRI Pro 1 Surakarta in reaching rural areas through the Rural Broadcasting Program. The method in this research is descriptive using a qualitative approach. Based on the results of the research and discussion, it can be concluded that RRI Pro 1 Surakarta broadcasts on 101.1 FM has the power to build a broadcasting strategy in reaching rural areas through rural broadcasting programs using the Prigle Starr-Mccavit Broadcasting Strategy theory, namely program planning Prepare short, medium and long term planning In the long term, program production is in the program production process, RRI Pro 1 Surakarta adjusts programs produced by RRI Pusat, in the sense that all RRI programs throughout Indonesia are produced by RRI itself, program execution in program execution, RRI Pro 1 Surakarta uses clock format system, namely the time that distinguishes morning, afternoon, evening and night and program evaluation in the program evaluation process, RRI Pro 1 Surakarta evaluates every 6 months.